Does empirical evidence support perceptual mindreading? - Smortchkova, J (Wiley, 2020)
According to perceptual accounts of mindreading, we can see, rather than cognize, other people's mental states. On one version of this approach, certain mental properties figure in the contents of our perceptual experiences. In a recent paper, Varga has appealed to empirical research to argue that intentions and emotions can indeed be seen, rather than cognized. In this paper, I argue that none of the evidence adduced to support the perceptual account of mindreading shows that we see mental properties, as opposed to non‐mental properties.